DFT Calculation, Hirshfeld Analysis and X-Ray Crystal Structure of Some Synthesized N-alkylated(S-alkylated)-[1,2,4]triazolo[1,5-a]quinazolines - Hatem A. Abuelizz; Saied M. Soliman; Hazem A. Ghabbour; Mohamed Marzouk; Mohamed M. Abdellatif; Rashad Al-Salahi (Crystals, 2021)
The present work aimed to synthesize 2-methylthio-triazoloquinazoline derivatives and study their X-ray, NMR, DFT and Hirshfeld characteristics. The cyclocondensation of dimethyl-N-cyanodithiocarbonate with 2-hydrazinobenzoic acid hydrochloride resulted in an intermediate, 2-methylthio-[1,2,4]triazolo[1,5-a]quinazolin-5-one (A), which upon treatment with phosphorus pentasulfide, transformed into the 2-methylthio-[1,2,4]triazolo[1,5-a]quinazolin-5-thione (B). Reaction of 2-methylthio-triazoloquinazolines (A&B) with alkyl halides (allyl bromide and ethyl iodide) in basic medium afforded 4-allyl-2-methylthio-[1,2,4]triazolo[1,5-a]quinazolin-5-one (1; N-alkylated) and 5-ethylthio-2-methylthio-[1,2,4]triazolo[1,5-a]quinazoline (2; S-alkylated), respectively. Their molecular and supramolecular structures were presented. Unambiguously, the molecular structures of 1 and 2 were confirmed via NMR and single-crystal X-ray diffraction. The resulting findings confirmed the structures of 1 and 2 and determined their crystalized system (monoclinic system; P21/n space group). Hirshfeld analysis of 1 revealed the importance of the significantly short O···H (6.7%), S···S (1.2%) and C···C (2.8%); however, the short H···H (42.6%), S···H (16.3%) and C···C (4.3%) were showed in 2 by intermolecular interactions in the molecular packing. The 1,2,4-triazoloquinzolines (1&2) were anticipated to be relatively polar compounds with net dipole moments of 2.9284 and 4.2127 Debye, respectively. The molecular electrostatic potential, atomic charge distribution maps and reactivity descriptors for 1 and 2 were also determined. The calculated nuclear magnetic resonance spectra of the targets 1 and 2 were well correlated with the experimental data.